Accrual accounting in Italian universities: a technical perspective. Issue 6 (10th August 2015) - Agasisti, Tommaso; Catalano, Giuseppe; Di Carlo, Ferdinando; Erbacci, Angelo
Abstract : Purpose: – The purpose of this paper is to examine the impact of full accrual accounting on the Italian public universities and, in this context, how some technical-accounting problems typical of public sector (recognition and valuation issues) have been addressed. An additional purpose investigated in this paper is the role of International Public Sector Accounting Standards (IPSASs) in helping to overcome these technical-accounting issues, for the case under examination. Design/methodology/approach: – The paper involves studying whether, and to what degree, some of the accounting choices made by the universities complied with the principles of full accrual accounting for several specific accounting registrations characterised by the presence of recognition and valuation issues. During this investigation, the paper also analyses whether the universities followed the accounting rules set out by the IPSAS Board. Findings: – The findings highlight that, in general, there is a low degree of compliance with full accrual accounting principles and they also revealed that IPSASs do not provide any detailed guidelines that can help universities in overcoming the recognition and valuation problems typical of the public sector. Originality/value: – The analysis presented in the paper confirms the findings of previous literature identifying a low level of compliance to full accrual accounting principles. This research shed light also on the longstanding debate about the role of IPSASs in promoting full accrual accounting in the public sector, revealing the scarce contribution of IPSASs to this process.